History of Medicine Ishaq bin Ali al-Rohawi: Pioneer in Medical Ethics - Haque, Anwar Ul (International Journal of Pathology, 2019)
Ethics is the foundation of all healthy developments and human progress in all spheres. Truth is life, and lie is death said the Prophet Muhammad ﷺ. When the world was in dark ages the Islamic world had glittering civilization and there was a big bang in all fields of science and humanities. The human uplift occurred at jet speed and was complete and comprehensive. Almost all modern sciences were founded in that era. It’s no exaggeration although it may seem so. A glance at Wikipedia will give you the names of hundreds of great scientists in that era. Islam instilled highest moral and ethical values as well as intense love for research with utmost honesty. Few people know that Khalifa Waleed predecessor of Khalifa Haroon Rashid had pioneered the medical licensing. Khalifa himself used to preside over the board of highly competent physicians of that time in competence examination of the clinicians before granting them license to practice. When Muslims downfall began in Spain, the medical licensing was taken over by the Italians.